2017
DOI: 10.1186/s13071-017-2053-4
|View full text |Cite
|
Sign up to set email alerts
|

The enzootic life-cycle of Borrelia burgdorferi (sensu lato) and tick-borne rickettsiae: an epidemiological study on wild-living small mammals and their ticks from Saxony, Germany

Abstract: Background Borrelia burgdorferi (sensu lato) and rickettsiae of the spotted fever group are zoonotic tick-borne pathogens. While small mammals are confirmed reservoirs for certain Borrelia spp., little is known about the reservoirs for tick-borne rickettsiae. Between 2012 and 2014, ticks were collected from the vegetation and small mammals which were trapped in Saxony, Germany. DNA extracted from ticks and the small mammals’ skin was analyzed for the presence of Rickettsia spp. and B. burgdorferi (s.l.) by qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 86 publications
3
34
5
Order By: Relevance
“…Detection of B. burgdorferi (s.l.) in rodent populations from Germany with infection rates up to 49.1% confirmed the role of these small mammals as reservoir hosts [40,42]. The collection sites for ticks in the current study are extensive forest areas that could contain high abundance of voles or other rodents acting as infected reservoir hosts for the local tick population.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Detection of B. burgdorferi (s.l.) in rodent populations from Germany with infection rates up to 49.1% confirmed the role of these small mammals as reservoir hosts [40,42]. The collection sites for ticks in the current study are extensive forest areas that could contain high abundance of voles or other rodents acting as infected reservoir hosts for the local tick population.…”
Section: Discussionsupporting
confidence: 72%
“…The overall prevalence of B. burgdorferi (s.l.) is lower compared to the infection rates registered in other studies from Germany [15,16,[40][41][42]. However, a previous study reported similar infection rates in I. ricinus ticks (16.8% of females, 12.9% of males and 5.7% of nymphs) collected in 2003 from woodlands in Mecklenburg-Western Pomerania [43], potentially indicating a constant circulation of B. burgdorferi (s.l.)…”
Section: Discussionmentioning
confidence: 70%
“…In Europe, six rickettsial pathogens— R. helvetica, R. raoultii, R. slovaca, R. conorii and R. felis —have been detected in rodents using molecular methods: R. helvetica in A. flavicollis, Apodemus sylvaticus, Apodemus agrarius, M. glareolus and Mus musculus [8] , R. raoultii in A. flavicollis and M. glareolus [14] , [15] , R. slovaca in Apodemus spp. [16] , R. conorii in A. sylvaticus and M. glareolus [1] and R. felis in A. flavicollis [15] . S. araneus has been found (based on serologic investigation) to be susceptible to R. helvetica infection [17] .…”
Section: Discussionmentioning
confidence: 99%
“…l .) by qPCR (C t < 33) were further examined by single-locus sequence typing targeting the recG gene (722 bp) [ 20 , 21 ]. Conventional PCRs were carried out in the Eppendorf MasterCycler Gradient Thermal Cycler (Eppendorf AG, Hamburg, Germany) and the products were visualized by gel-electrophoresis on 1.5% agarose gel stained with Midori Green (NIPPON, Genetics, Düren, Germany).…”
Section: Methodsmentioning
confidence: 99%